L'insertion économique internationale du continent africain - Grégoire, Luc (Études internationales, 1991)
With a GDP of355 million dollars, i.e. 4 % of the world GDP, the African continent is economically the least developed region. During the 1980s Africa underwent economic and social decline combined with worsening external and internal financial imbalances. The Maghreb, southern Africa, and Nigeria constitute nonetheless areas that have a relatively high level of development with much potential.